Helping abused children and their families : towards an evidence-based practice model - Trotter, Chris (Thousand Oaks, Calif. : SAGE, 2004)
This is a guide to the main challenges faced by social workers working in the context of child abuse and child protection. The book outlines the knowledge and skills needed for effective practice and shows how certain approaches to intervention can help to prevent re-abuse.